Tata Kelola Pembelajaran Blended Learning Pada Era Pandemi Covid-19 (Studi Universitas Prof. Dr. Hazairin, SH) - Annisa Amaliah; Henny Apriyanty; Alexsander Alexsander (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
This study aims to examine and to analyze the effect of emotional intelligence, employee competence, and job satisfaction on the performance of educators and education staff in blended learning management in the Covid-19 pandemic era. Using primary data collected through interviews with leaders at the University, Prof. Dr. Hazairin, SH Bengkulu, and used a questionnaire, secondary data was collected through journals, books, and other publications. This research uses survey research methods and verification descriptive research methods with a quantitative approach. The subjects studied were 169 people consisting of 104 educators and 65 UNIHAZ staff from a total population of 222 people and data analysis using SEM (Structural Equation Modeling) with LISREL 8.72 program. The results of this quantitative study indicate that emotional intelligence, employee competence, and job satisfaction have a significant effect on the performance of educators and education staff, the effective contribution given by the variables of emotional intelligence, employee competence, and job satisfaction of each variable is 52% fixed for the performance variable. , there are still 48% of other factors. However, emotional intelligence, employee competence, and job satisfaction through the performance of educators and ed0ucation have a negative but significant effect on blended learning in the Covid-19 pandemic era, this is because the results obtained by blended learning are low in negative complexes. -2.47 so that there is an increase in managing blended learning. Measuring performance has been done with IT-based assessments, not using manual assessments, so the performance that employees will give will be maximized.